THE RELATIONSHIP BETWEEN MOTHER'S PARENTING STYLES AND STUNTING IN TODDLERS AGED 24-59 MONTHS IN THE WORKING AREA OF PUSKESMAS KUTA BARO THE DISTRICT OF ACEH BESAR - Jafar, Rofilatunisa; Fithriany; Fatma (Journal of Midwifery and Community Health (JMCH), 2023)
Introduction: It is estimated that around 26% of children under five worldwide are stunted. Indonesia is included in 17 countries out of 117 countries in the world that have a high prevalence of wasting, stunting, and over being weight in toddlers. Nusa Tenggara Timur (NTT) is the province that has the highest prevalence of stunting, while Aceh is in the third position. The district of Aceh Besar is ranked 18th out of 23 districts/cities in Aceh Province with a high incidence of stunting. The sub-district of Kuta Baro is the third rank with the highest stunting in the district of Aceh Besar; with 272 cases of stunting. One of the indirect causes of stunting is the mother,s parenting style. Method: This study was an analytical observational study with a cross sectional-section aligned to analyze the relationship between mothers’ parenting styles and the incidence of stunting in toddlers aged 24-59 months. Collecting data using a questionnaire. Result: The incidence of stunting in toddlers aged 24-59 months in the working area of Puskesmas Kuta Baro was 43.3%. The results of the bivariate analysis showed that there was a significant relationship between food parenting, health parenting, and psychosocial stimulation with stunting in toddlers at Puskesmas Kuta Baro (P <0.05), meanwhile hygiene and environmental sanitation did not relationship with stunting (P=0.971). Conclusion: There was a significant relationship between food parenting style, health parenting style, and psychosocial stimulation parenting style with the incidence of stunting in toddlers.